Analisis Penilaian Kinerja Keuangan Menggunakan Metode Rgec Pada Bank Swasta Periode 2020-2022 - Oktarina, Hani; Merina, Citra Indah (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
This research aims to assess the financial performance of national private commercial banks during the 2020-2022 period using the RGEC method, which includes Risk Profile, Good Corporate Governance (GCG), Financial Performance and Capital. Evaluation of bank health is carried out through financial ratios: NPL and LDR for Risk Profile, self-assessment for GCG, ROA, ROE, NIM, and BOPO for Financial Performance, and CAR for Capital. Research findings show that in 2020, these banks were categorized as "very healthy" (PK-1), remained with the "very healthy" (PK-) title in 2021, and decreased to "very healthy" (PK-1 ) in 2022. The period 2020 to 2022 shows that the national private commercial banks studied maintain a "very healthy" (PK-1) status consistently. This indicates that these banks have succeeded in maintaining excellent quality financial performance despite facing challenges and market dynamics that may have changed during that period. A stable assessment in the (PK-1) category shows that these banks have succeeded in managing risk effectively, implementing good corporate governance, and showing solid financial performance and adequate capital. Stability in this predicate also reflects the bank's resilience to economic fluctuations and their ability to deal well with various market conditions.